2017
DOI: 10.1155/2017/8920356
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses in Human Dental Pulp Stem Cells Treated with Three Endodontic Materials

Abstract: Human dental pulp stem cells (HDPSCs) are of special relevance in future regenerative dental therapies. Characterizing cytotoxicity and genotoxicity produced by endodontic materials is required to evaluate the potential for regeneration of injured tissues in future strategies combining regenerative and root canal therapies. This study explores the cytotoxicity and genotoxicity mediated by oxidative stress of three endodontic materials that are widely used on HDPSCs: a mineral trioxide aggregate (MTA-Angelus wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 65 publications
3
39
0
1
Order By: Relevance
“…Indeed, in vitro assays with cell cultures are commonly used to investigate cell behavior and biological responses in specific situations. The results of these in vitro assays are relevant to clinical conditions and provide an appropriate model for screening the properties of different dental materials prior to in vivo studies.…”
mentioning
confidence: 99%
“…Indeed, in vitro assays with cell cultures are commonly used to investigate cell behavior and biological responses in specific situations. The results of these in vitro assays are relevant to clinical conditions and provide an appropriate model for screening the properties of different dental materials prior to in vivo studies.…”
mentioning
confidence: 99%
“…In terms of the material setting condition, 23 studies evaluated root canal sealers in fresh or freshly mixed state, 15 in set condition with 24 h incubation, 15 in both freshly mixed and set conditions, and 20 in a set condition with other or multiple times of incubation. Concerning the cell models used for cell viability assessment (Table A2), several studies used cultures of human cells, namely: dental follicle-derived mesenchymal stem cells [23], tooth germderived stem cells [40], bone marrow-derived mesenchymal stem cells [49], gingival fibroblasts [31,[50][51][52][53][54][55][56], dental pulp stem cells [57], osteoblasts [23,41,46,[58][59][60][61], periodontal ligament cells [26,28,39,45,48,[62][63][64][65][66], human osteoblast-like cells (MG63) [38,42,67,68], cervical carcinoma cells or human cervical carcinoma cells (HeLa) cells [33,37] and THP-1 human monocytic cells [36]. Other cell…”
Section: Resultsmentioning
confidence: 99%
“…However, a cytotoxic effect of bioactive sealers was also reported in comparison with other materials, either similar-compared to epoxy resin-based [23,51,64,73,74] or calcium hydroxide-based [26] sealers-or lower compared to zinc oxide-eugenol-based [39,41,45,46,66,74,75], epoxy resin-based [23,39,40,49,52,61,66,[73][74][75][76], methacrylate resin-based [39,41], or other materials [67]. Some studies reported a higher cytotoxic effect of MTA Fillapex ® compared with epoxy resin-based sealers in set condition [23,40,51,57,61,66,71]. Although one study [51] showed no cytotoxic effect by Endosequence BC TM , one study [49] showed lower cytotoxicity than the epoxy resin-based AH Plus TM and similar to BioRoot TM RCS, and one study [43] showed a higher cytotoxicity compared to AH Plus TM in set material conditions but lower than PCS.…”
Section: Cytotoxicity Of Root Canal Sealersmentioning
confidence: 99%
“…At the conclusion of the setting time, there are a decreasing number of hydroxyl ions, thus neutralizing the pH. Loushine et al found that bioceramic sealers required a final setting time of 160-240 h and released elements that affected the viability of periodontal ligament cells [18,19].…”
Section: Discussionmentioning
confidence: 99%